2017
DOI: 10.1186/s12879-016-2105-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multidrug-resistant organisms in refugee patients, medical tourists and domestic patients admitted to a German university hospital

Abstract: BackgroundPatients with contact to healthcare-system in high-prevalence countries (HPC) and refugee patients in hospital settings (REF) have previously been identified to be at risk of carrying multidrug-resistant organisms (MDRO). Comparative studies addressing the epidemiology of MDRO in patients transferred from hospitals abroad (ABROAD) and REF are lacking but are necessary to introduce refined infection control measures.MethodsFrom December 2015 to June 2016, 117 REF, 84 ABROAD and 495 patients admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
41
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 37 publications
11
41
1
Order By: Relevance
“…Our findings regarding the timescale of associations of leptospirosis and precipitation are consistent with those reported in similar studies in rural settings [7,8,22,57]. On the other hand, we found an association between leptospirosis incidence and wet soils, when prior studies reported associations with indicators for flooding [3,19,26,56].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings regarding the timescale of associations of leptospirosis and precipitation are consistent with those reported in similar studies in rural settings [7,8,22,57]. On the other hand, we found an association between leptospirosis incidence and wet soils, when prior studies reported associations with indicators for flooding [3,19,26,56].…”
Section: Discussionsupporting
confidence: 91%
“…As a result, individuals who have symptoms of TB are expected to seek TB diagnostic services by traveling long distance. Hence, the individuals might be delayed or not seek the services at all [12,16]. This could be related to the country's economy in availing TB diagnostic centers at the community level, and poor rural residents not able to afford costs related to transportation and investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, self-treatment, limited community awareness of the risks associated with delayed care seeking and low educational status are all factors significantly associated with delayed TB care seeking. Among those who have not had previous TB treatment, and who have not had a cough for a long duration, there is a delay in TB care seeking [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the beds in the ICU are very few, and the increase of MDRI makes the medical resources not properly configured. Previous studies [24,25] have concluded that the hospitalization time of patient needs to be strictly controlled, which is one of the effective measures to prevent MDRI. Mechanical ventilation can significantly increase the chance of respiratory infection [26,27].…”
Section: Discussionmentioning
confidence: 99%